2015
DOI: 10.1186/s12891-015-0551-0
|View full text |Cite
|
Sign up to set email alerts
|

New physical examination tests for lumbar spondylolisthesis and instability: low midline sill sign and interspinous gap change during lumbar flexion-extension motion

Abstract: BackgroundLumbar spondylolisthesis (LS) and lumbar instability (LI) are common disorders in patients with low back or lumbar radicular pain. However, few physical examination tests for LS and LI have been reported. In the study described herein, new physical examination tests for LS and LI were devised and evaluated for their validity. The test for LS was designated “low midline sill sign”, and that for LI was designated “interspinous gap change” during lumbar flexion-extension motion.MethodsThe validity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 13 publications
1
30
1
1
Order By: Relevance
“…The instability is due to the facet joints tending to align closest to the sagittal plane. 35 , 50 Interestingly, the youngest patient with radiological lumbar instability in the present study was 23 years’ old, which was concordant with that of a previous study 7 in which the authors reported that instability started in patients in their 20 s. They suggested that those patients could have been in the initial stage of disk degeneration. 7 …”
Section: Discussionsupporting
confidence: 92%
“…The instability is due to the facet joints tending to align closest to the sagittal plane. 35 , 50 Interestingly, the youngest patient with radiological lumbar instability in the present study was 23 years’ old, which was concordant with that of a previous study 7 in which the authors reported that instability started in patients in their 20 s. They suggested that those patients could have been in the initial stage of disk degeneration. 7 …”
Section: Discussionsupporting
confidence: 92%
“…)0.59 (? )Spondylolisthesis Studies supporting a diagnostic rule  Manual hypermobility test positive (P) Fritz 2005 [87]0.46 (0.30–0.64)0.81 (0.60–0.92)2.4 (0.9–6.4)0.66 (0.44–0.99)  Lack of manual hypomobility test positive (P) Fritz 2005 [87]0.43 (0.27–0.61)0.95 (0.77–0.99)9.0 (1.3–63.9)0.60 (0.43–0.84)  Lack of manual hypomobility test positive and flexion ROM > 53° (P) Fritz 2005 [87]0.29 (0.13–0.46)0.98 (0.91–1.00)12.8 (0.8–211.6)0.72 (0.55–0.94)  Manual flexion hypermobility test positive (P) rotation Abbott 2005 [88]0.05 (0.01–0.36)0.99 (0.96–1.00)4.1 (0.2–80.3)0.96 (0.83–1.11)  Manual flexion hypermobility test positive (P)translation Abbott 2005 [88]0.05 (0.01–0.22)0.99 (0.97–1.00)8.7 (0.6–134.7)0.96 (0.88–1.05)  Manual extension hypermobility test positive (P) rotation Abbott 2005 [88]0.22 (0.06–0.55)0.97 (0.94–0.99)8.4 (1.9–37.6)0.80 (0.56–1.13)  Manual extension hypermobility test positive (P) translation Abbott 2005 [88]0.16 (0.06–0.38)0.98 (0.94–0.99)7.1 (1.7–29.2)0.86 (0.71–1.05)  Slipping by palpation (P) Kalpakcioglu 2009 [90]0.88 (0.80–0.93)1.00 (0.89–1.00)NA0.12 (0.07–0.20)  Slipping by palpation (P) Collaer 2006 [91]0.60 (0.15–0.95)0.87 (0.73–0.96)4.7 (1.6–13.9)0.46 (0.16–1.35)  Passive lumbar extension test (P) Kasai 2006 [89]0.84 (0.70–0.93)0.90 (0.82–0.95)8.8 (4.5–17.3)0.18 (0.08–0.37)  Passive lumbar extension test (P) Ferrari 2014 [92]0.44 (0.29–0.59)0.86 (0.67–0.95)3.2 (1.1–9.7)0.65 (0.47–0.90) Studies not supporting a diagnostic rule  None Additional findings reported by more than one study  Slipping by inspection (P) Kalpakcioglu 2009 [90]0.21 (0.14–0.30)1.00 (0.89–1.00)NA0.79 (0.71–0.87)  Slipping and Sill sign by inspection and palpation (P) Ahn 2015 [93]0.81 (0.65–0.91)...…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Ebrahimzadeh et al (1996) in Iran, 13 patients were women and 7 men (12). Kalpakcioglu et al (2009) in one study and Ahnand Jhun (2015) in another one reported that the number of women was higher than men (13,14). The most common type of spondylolisthesis was degenerative (95.2%).…”
Section: Discussionmentioning
confidence: 96%